Applied Sectors for Psychologists - Puntiroli, Michael (My University, 2020)
Invited to give an annual talk on "Applied Sectors for Psychologists" aimed at inspiring psychology Masters students on how they can make use of their psychology knowledge to help solve concrete world problems as part of governmental projects or within business.
, Applied Sectors for Psychologists, Geneva
Keywords: Applied Psychology